O impacto econômico das cultivares no agronegócio e a repercussão jurídica - Calegari, Samanta (Universidade do Vale do Rio dos Sinos, 2023)
Intellectual property plays an important role in generating innovation in a country and there is the intention to developers to have a return on their investment. The objective of this research is to analyze intellectual property rights relating to plant breeding activities in the country – with a special focus on the protection of plants through cultivars and the impacts that this protection has had on agribusiness, mainly in the seed sector. This examination adopts an economic perspective, its effects on agribusiness, observing farmers' practices about this protection, and the system proposed by the Cultivar Protection Law, exploring the importance of developing innovations in the field. The study of the legislative framework will focus on the aforementioned law, examining its systematics in conjunction with other legislation on the subject, especially observing the farmer's behavior and the exceptions provided for in the legislation about cultivars, as well as the repercussions of the use of two forms of plant protection in the country and the differences between protection through the cultivar system and the patent system. To accomplish this, the research methodology hinges upon the application of Inductive Thinking, complemented by an exhaustive bibliographic review, spanning both domestic and international sources, in pursuit of an exploratory objective. The research points out that the lack of adequate legislation in the current context, without objective criteria, and the lack of compatibility of plant protection systems in the country, generate insecurity and a lack of knowledge about the aspects pertinent to users of the technologies developed, eroding so are the creators of these.
Keywords: Agronegócio; Cultivares; Patentes; Propriedade intelectual; Proteção de plantas; Agribusiness; Cultivated variety; Intellectual property; Variety protection; ACCNPQ::Ciências Sociais Aplicadas::Direito